Design of an Advanced Phasor Data Concentrator for Monitoring of Distributed Energy Resources in Smart Microgrids - Pourramezan, Reza; Seyedi, Younes; Karimi, Houshang; Guchuan Zhu; Mont-Briant, Michel (IEEE transactions on industrial informatics, 2017)
Synchrophasor networks are subject to communication delays and packet dropout that can compromise data integrity and, thus, jeopardize control and monitoring of smart microgrids. This paper proposes an advanced phasor data concentrators (APDC) capable of counteracting the communication impairments and improving the quality of monitoring of distributed energy resources (DERs) in microgrids. The proposed APDC utilizes an adaptive compensation scheme to achieve an effective estimate of missing data elements. Moreover, a monitoring unit is proposed to reliably detect frequency excursions and identify the DERs affected by islanding events. The performance of the proposed APDC is evaluated based on realistic phasor measurement unit data aligned and processed with real-time OpenPDC software. The experimental results confirm a high-level data integrity under both normal and disturbed conditions of microgrids. Moreover, fast and reliable detection of islanding events is achieved due to the significant improvement in detection time even under severe data losses.